Braindance Activities Based on Minang Dance Basic Movements in Children Ages 5-6 Years Old - Yetti, Elindra; Syarah, Erie Siti (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2021)
Braindance activities based on Minang dance basic movements are moving activities carried out by children aged 5-6 years at an early childhood education institution in Bukittinggi City since 2019 when the trial results of the development of braindance based on the Minang dance basic movements were implemented at the Early Childhood Institutions. This study aims to (1) examine the uniqueness of the braindance movement based on the Minang dance basic movements, (2) examine the growth and development of children that appear after participating in the braindance activities, (3) examine the situation and condition of the child in the Minang braindance activities. This study used qualitative methods with data collection techniques through observation, interviews, and documentation. Data analysis was carried out with the stages of condensation, data presentation, and drawing conclusion. Data validation was carried out using triangulation of techniques, sources, and time. The study was conducted on fifteen students aged 5-6 years at an early childhood education institution in Bukittinggi. The results showed that: (1) Braindance based on Minang dance basic movements is an activity that combines gymnastic movements with the basic movements of Minang dance, as well as Minang music accompaniment; (2) Children’s motor skills become better, children can coordinate movement, brain, and feelings, and children’s creativity becomes more developed; (3) Minang braindance activities are fun for children.